Enhancing stability of aerobic granules by microbial selection pressure using height-adjustable influent strategy. (1st August 2021) - Zhou, Jia-heng; Ren, Qing; Xu, Xiao-lei; Fang, Jing-yuan; Wang, Tao; Wang, Kan-ming; Wang, Hong-yu
Highlights: Optimal size range was proposed regarding mass transfer and granules stability. Height-adjustable influent strategy was used to optimize size distribution. Propagation of Thiothrix sp. in oversized granules caused filamentous bulking. Exceeded hydraulic shear stress decreased abundance of SND bacterium. Optimize size distribution facilitated enrichment of SND bacterium and stability. Abstract: Optimizing granules size distribution is critical for both reactor performance and stability. In this research, an optimal size range of 1800 to 3000 μm was proposed regarding mass transfer and granules stability based on granules developed at DO around 8.0 mg L −1 with the feed COD:N:P at 100:5:1. A height-adjustable influent strategy was applied to facilitate the nutrient storage of granules at optimum size range via microbial selective pressure. Results suggested insufficient hydraulic shear stress led to overgrowth of granules size. High abundance of filamentous bacteria ( Thiothrix sp.) was observed in oversized granules, which detached and affected the remaining granules, resulting in severe sludge bulking. Strong hydraulic shear stress suppressed uncontrolled growth of granules. However, fewer abundance of simultaneous nitrification and denitrification (SND) bacterium was acquired, which led to unfavored SND effect and total nitrogen (TN) removal efficiency. The height-adjustable influent strategy facilitated the poly-β-hydroxybutyrate (PHB) storage of granules at optimum size range, while limiting the overgrowth of granules size. Additionally, more than 87.51% of total granules situated in optimal sizes range, which led to higher abundance of SND bacterium and higher TN removal efficiency. Graphical abstract: Image, graphical abstract